Effect of inulin in pineapple jam: physicochemical and sensory analysis among school children - Kétlin Ariane Santos; Priscila Naiverth Faix; Elisvânia Freitas dos Santos; Maria Raquel Manhani; Érica Caroline da Silva; Daiana Novello (O Mundo da Saúde)
The present study aimed to evaluate the sensory acceptability of traditional formulations pineapple jam of inulin additions among school children. We also intended to determine the physicochemical composition of the traditional product and that having a higher amount of inulin and acceptance similar to standard. The following pineapple jam formulations were developed: F1 (standard) and the other ones with 4% (F2), 8% (F3), 12% (F4) and 16% (F5) of additional inulin. Sixty non trained tasters, both genders, aged from 7 to 10 years were invited to participate in sensory evaluation. The attributes of appearance, aroma, taste, texture and color were evaluated, and also the overall acceptance and purchase intent. On physicochemical analysis, moisture, ash, proteins, lipids, carbohydrates, dietary fiber and caloric value content were determined. The samples did not show substantial differences among them in none of the evaluated attributes, and the tasters showed great sensory acceptance. Comparing F1 with F5 in the physicochemical analysis, we saw F1 presented higher carbohydrate content than F5. There were no substantial differences among crude ash, proteins and lipids in both formulations. F5 presented the highest moisture content and dietary fiber amount. Products elaboration allowed us to prove that by adding up to 16% of inulin in pineapple jam, the tasters had a great sensory acceptance, similar to that to the standard product, with good marketing expectations and improvements in the food nutritional composition.